EVALUASI PRESTASI OLAHRAGA SEPAK TAKRAW PERSPEKTIF SPORT SCIENCE DI KABUPATEN GRESIK - Hanafi, Moh; Hakim , Luqmanul; Muhyi, Muhammad (YLPK Mahardhika, 2024)
The 2023 East Java Provincial Sports Week (PORPROV) Edition Eight has been held in four districts: Sidoarjo, Mojokerto, Mojokerto City, and Jombang. The event ran smoothly, and the medal tally achieved by Gresik Regency, with 28 Gold, 45 Silver, and 48 Bronze, placed them in 7th position in the standings. Out of 121 medals in the Sepak Takraw Sports branch, no medals have been contributed from the 5 events contested, and in 2 consecutive PORPROV events, Gresik's Sepak Takraw team was eliminated in the quarter-finals. This research is a descriptive study with a quantitative approach. Quantitative refers to information that is quantified. The method used to collect data is a survey with questionnaires, where the data collection technique involves providing concepts with various values. The design of this research uses the survey method, which involves sampling from a population and using a questionnaire as the primary data collection tool. The results of the study on the Biomechanics Pillar and the Rehabilitation Pillar have Very High Validity, with a correlation above 0.90 considered valid. Whereas the Physical Pillar, Psychological Pillar, and Nutritional Pillar have High Validity: Correlation 0.80 - 0.89 indicates a High relationship. And the Health Pillar has Moderate Validity. A correlation of 0.70 – 0.79 indicates moderate validity.